Derivación de valores económicos de la producción de leche de bovinos en la parroquia Mulaló utilizando funciones de beneficio. - Ochoa Bravo, Sharon Janeth (2022)
Due to lack of a genetic improvement plan for bovines Ecuador, the poor farmers management and low knowledge in their farms, milk production is inefficient, therefore, a descriptive research has been conducted in order to determine the economic values of bovine milk production on Cotopaxi province, Latacunga city - Mulaló parish, which is set to be genetic baseline of improvement project. The research included 235 bovines from 34 producers to whom the project was socialized to strengthen and discuss key points to be developed, and data collection was applied to the owners through surveys of each cattle. As a result, 132 cattle are producing cows (56.2%), female sex (95.3%), Holstein predominates the parish (79.3%), daily weight gain (800 g/day), negative to California mastitis test (84.6%), most purchased feed green banana (30%), balanced with (26%); milk costs range from 0.38 to 0.43 cents at the parish. At the end of data collection, selection of criteria were determined by the gain weight, density and open days. This research is the basis for genetic selection of criteria associated to cattle production systems and selecting the best cattle for genetic improvement.